Desvendando a matemática do GPS - Lima, Davi Dantas (2013)
The purpose of this monograph is to study the mathematical principles behind the Global Positioning System, the so-called GPS. We start with a historical approach of the evolution of this technology. Then we show some theorems in geometry: plane, spatial and analytic, which together with some physical principles (average speed, speed of light, the Doppler effect,...) guided the creators of this powerful tool that determines with remarkable accuracy the position (latitude, longitude and altitude) of a transmitter. Finally, we suggest activities to be performed at the level of basic education, to stimulate students curiosity by scientific knowledge contained therein.